Laparoscopic wedge resection in a late second trimester cornual pregnancy - Anis Iryani Safiee; Wan Ahmad Hazim Wan Ghazali (Wolters Kluwer Medknow Publications, 2021)
Cornual pregnancy happens when implantation occurs in the cavity of a rudimentary horn of the uterus, which may or may not be communicating with the uterine cavity. The diagnosis of cornual pregnancy remains challenging, and rupture of a cornual pregnancy usually causes massive bleeding. Early diagnosis and treatment, therefore, are very crucial and key to prevent mortality. Historically, the management of cornual pregnancies included wedge resection through open surgery or even hysterectomy. In this case report, we would like to highlight a case of late second trimester cornual pregnancy, at 19-week and 3-day gestation, which was managed laparoscopically.